IgE-mediated enhancement of CD4+ T cell responses in mice requires antigen presentation by CD11c+ cells and not by B cells. - Frida Henningsson (Public Library of Science (PLoS), 2011)
IgE antibodies, administered to mice together with their specific antigen, enhance antibody and CD4(+) T cell responses to this antigen. The effect is dependent on the low affinity receptor for IgE, CD23, and the receptor must be expressed on B cells. In vitro, IgE-antigen complexes are endocytosed via CD23 on B cells, which subsequently present the antigen to CD4(+) T cells. This mechanism has been suggested to explain also IgE-mediated enhancement of immune responses in vivo. We recently found that CD23(+) B cells capture IgE-antigen complexes in peripheral blood and rapidly transport them to B cell follicles in the spleen. This provides an alternative explanation for the requirement for CD23(+) B cells. The aim of the present study was to determine whether B-cell mediated antigen presentation of IgE-antigen complexes explains the enhancing effect of IgE on immune responses in vivo. The ability of spleen cells, taken from mice 1-4 h after immunization with IgE-antigen, to present antigen to specific CD4(+) T cells was analyzed. Antigen presentation was intact when spleens were depleted of CD19(+) cells (i.e., primarily B cells) but was severely impaired after depletion of CD11c(+) cells (i.e., primarily dendritic cells). In agreement with this, the ability of IgE to enhance proliferation of CD4(+) T cells was abolished in CD11c-DTR mice conditionally depleted of CD11c(+) cells. Finally, the lack of IgE-mediated enhancemen of CD4(+) T cell responses in CD23(-/-) mice could be rescued by transfer of MHC-II-compatible as well as by MHC-II-incompatible CD23(+) B cells. These findings argue against the idea that IgE-mediated enhancement of specific CD4(+) T cell responses in vivo is caused by increased antigen presentation by B cells. A model where CD23(+) B cells act as antigen transporting cells, delivering antigen to CD11c(+) cells for presentation to T cells is consistent with available experimental data.